Identifying and Evaluating Large Scale Policy Interventions : What Questions Can We Answer? - Dhungana, Sandesh (2012)
Using a data-driven empirical case study method, the paper evaluates the impact of one identified reform program on development outcomes. The paper uses the World Bank Country Policy and Institutional Assessment Ratings to identify large scale structural and macro-level policy interventions in the last decade that were seen as being sustained and successful for IDA countries. Robustness checks are performed to show the efficacy of the method in particular cases. It was found that the method attains robustness in the case of Nigeria.